Fuel cell catalyst, preparation method thereof and fuel cell

By combining oxygen atmosphere oxidation and ammonia atmosphere ammonia treatment, the problem of the antagonism of nitrogen and oxygen doping elements in fuel cell catalysts is solved, the catalytic performance and durability of the catalyst are improved, and the efficient carbon support is achieved The mass production of nitrogen doping is solved by controlling the mass production of nitrogen, which solves the problems of insufficient catalyst performance and difficulty in mass production in the prior art.

CN119181812APending Publication Date: 2024-12-24STATE POWER INVESTMENT CORP HYDROGEN ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411245352.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In the existing preparation methods of fuel cell catalysts, nitrogen and oxygen doped fuel cell catalysts have insufficient performance and are difficult to mass production. The effects of doped elements antagonize each other, resulting in insufficient catalytic activity and durability.

Method used

Using a combination of oxygen atmosphere oxidation treatment and ammonia atmosphere ammonia treatment, the nitrogen and oxygen doping content in carbon materials is adjusted step by step, the dispersion uniformity of active metals and the loading ratio in the pores is improved, and the doping elements are avoided. Antagonize each other to achieve high load and high dispersion catalyst preparation.

Benefits of technology

The catalytic performance and durability of the catalyst are significantly improved, and the efficient mass production of controlled nitrogen doping of carbon support is achieved, which reduces production costs and risks, and enhances the dispersion of the active metals and the loading ratio in the pores of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181812A_ABST
    Figure CN119181812A_ABST
Patent Text Reader

Abstract

The invention provides a fuel cell catalyst, a preparation method thereof and a fuel cell, and belongs to the technical field of fuel cells. The carbon material with high nitrogen and oxygen doping ratio is prepared by adopting a treatment method of combining oxygen atmosphere oxidation treatment and ammonia atmosphere ammonolysis treatment, the dispersion uniformity and in-hole loading ratio of a metal component taking the carbon material as a carrier are improved, and meanwhile, the dispersion uniformity and catalytic performance of resin on the surface of a catalyst are improved; besides, oxygen atmosphere oxidation treatment replaces a concentrated nitric acid oxidation method, oxygen-containing functional groups on the surface of the oxidized carbon carrier and the doping number of oxygen atoms are increased to serve as reaction sites in the ammonolysis nitrogen doping treatment process, the efficiency of ammonolysis nitrogen doping treatment is remarkably improved, and the nitrogen doping difficulty of the carrier is greatly reduced; the method is a mass production approach for realizing controllable nitrogen doping of the carbon carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a fuel cell catalyst and a preparation method thereof, and a fuel cell. Background Art

[0002] For example, carbon materials such as carbon nanotubes, carbon nanofibers, graphene, graphite powder, and carbon black have good physical and chemical properties and low cost, and are widely used as carbon carriers for the preparation of catalysts for fuel cells. The surface properties of carbon materials as catalyst carriers play a very important role in the preparation of catalysts and the activation process in catalytic reactions. Functionalizing the surface of carbon carriers to enrich the surface of carbon carriers with specific elements is a common method for obtaining highly active and durable catalysts.

[0003] According to literature reports, nitrogen doping of carbon powder materials is an important way to anchor the active components of the catalyst, improve the degree of resin dispersion, and reduce the poisoning of active metals. The preparation methods of nitrogen-doped carbon carriers mainly include synthesis, coating and ammonia decomposition. The synthesis method mainly obtains nitrogen-doped carbon carriers by carbonizing some nitrogen-containing organic matter and retaining the nitrogen element therein. The coating method mainly obtains a carbon powder material with a nitrogen-doped shell by impregnating commercial carbon powder materials with nitrogen-containing organic matter and then carbonizing them. The ammonia decomposition method mainly obtains nitrogen-doped carbon powder materials by high-temperature sintering of carbon powder in an ammonia atmosphere. However, the above treatment methods usually use high temperature or high pressure reaction conditions, and there are also disadvantages such as low yield of nitrogen-doped carbon carriers and difficult to control the degree of doping.

[0004] On the other hand, the second-generation Mirai fuel cell vehicle uses an alloy catalyst with a mesoporous carbon carrier. According to relevant reports, the oxygen content of the mesoporous carbon carrier used is 0.1-3wt%. The appropriate proportion of oxygen content on the carbon carrier can improve the hydrophilicity of the carbon carrier, while improving the dispersibility of the metal component, promoting the intrapore loading of the metal component. The methods for increasing the content of oxygen-containing functional groups in the carbon carrier mainly include oxidation method, impregnation method, etc. The oxidation method mainly uses a strong oxidant (such as potassium permanganate, etc.) to treat the carbon carrier, thereby introducing oxygen-containing functional groups to the surface of the carbon material. The impregnation method mainly involves immersing the carbon carrier in a solution containing an oxidant (such as concentrated nitric acid, etc.), and then drying and calcining the immersed carbon carrier to increase the surface oxygen content of the carbon carrier. However, the oxidation method and the impregnation method require the use of hazardous chemicals. These methods are not easy to apply to large-scale production and promotion. In addition, these methods will introduce impurities into the carbon material. In addition, the yield of the carbon carrier is also low.

[0005] Therefore, proposing a method for preparing a catalyst carbon carrier with a safe and reliable preparation process, easy mass production, and adjustable heteroatom doping ratio is of great significance for the preparation of supported high-activity and high-durability fuel cell catalysts. Summary of the invention

[0006] The present invention is based on the inventors' discovery and understanding of the following facts and problems: the preparation method of the fuel cell catalyst disclosed in the related art is only nitrogen doping or only oxygen doping, and the catalytic activity and durability of the obtained fuel cell catalyst are not high enough, which needs further in-depth research.

[0007] If nitrogen and oxygen are doped at the same time, the performance of fuel cell catalysts may be improved. When the method of pyrolysis of nitrogen-oxygen organic matter is used to prepare nitrogen- and oxygen-doped fuel cell catalysts, the single batch preparation amount of this method is usually small, the consistency between batches is also poor, and mass production is difficult; in addition, in the synthesis of fuel cell catalysts with high nitrogen and oxygen doping contents, the anchoring effect of nitrogen doping on active components and the promoting effect of oxygen doping on intrapore loading antagonize each other, weakening the effect of the two doping on the catalyst performance. Therefore, it is necessary to develop an adaptive fuel cell catalyst preparation process to give full play to the role of the two doping elements.

[0008] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the embodiments of the present invention provide a fuel cell catalyst and a preparation method thereof and a fuel cell.

[0009] A first aspect of an embodiment of the present invention provides a method for preparing a fuel cell catalyst, comprising the following steps:

[0010] S101, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier;

[0011] S102, loading a first active metal on the oxidized carbon support to obtain a first catalyst;

[0012] S103, performing a second sintering treatment on the first catalyst in an ammonia atmosphere to obtain a second catalyst;

[0013] S104, loading a second active metal onto the second catalyst to obtain the fuel cell catalyst.

[0014] The advantages and technical effects brought by the preparation method of the first aspect of the embodiment of the present invention are:

[0015] 1. Compared with the fuel cell catalyst preparation method that only performs nitrogen doping or only performs oxygen doping, the preparation method of the first aspect of the embodiment of the present invention adopts a treatment method that combines oxygen atmosphere oxidation treatment and ammonia atmosphere ammonia decomposition treatment to regulate the preparation of nitrogen and oxygen-doped carbon materials, thereby improving the dispersion uniformity and intrapore loading ratio of the active metal using the carbon material as a carrier, and also improving the dispersion uniformity of the resin on the catalyst surface during the subsequent preparation of the catalyst layer, thereby improving the catalytic performance of the catalyst layer.

[0016] 2. The fuel cell catalyst preparation methods of the related art that only carry out nitrogen doping or only carry out oxygen doping can achieve a low doping content of heteroatoms (nitrogen or oxygen) in the carbon material, while the preparation method of the first aspect of the embodiment of the present invention can greatly increase the doping content of heteroatoms (nitrogen and oxygen) in the carbon material, which is more conducive to improving the catalytic activity and durability of the catalyst.

[0017] 3. The preparation method of the first aspect of the embodiment of the present invention prepares a high-loaded supported catalyst by a step-by-step loading method. By performing the first loading on a carrier with a high oxygen-containing functional group, the in-pore loading ratio of the catalyst is increased. The material is subjected to a second loading after aminolysis, so that the active metal is anchored at the nitrogen-containing site, thereby ensuring the dispersion of the active metal in the high-loaded catalyst.

[0018] 4. The preparation method of the first aspect of the embodiment of the present invention adopts air oxidation method instead of concentrated nitric acid oxidation method, which increases the oxygen-containing functional groups and oxygen atom doping number on the surface of the carbon carrier after oxidation as reaction sites for the nitrogen doping process of ammonolysis treatment, significantly improves the efficiency of nitrogen doping by ammonolysis treatment, and greatly reduces the difficulty of nitrogen doping of the carrier. This method is a mass production approach to achieve controllable nitrogen doping of carbon carriers.

[0019] 5. Compared with the method of preparing nitrogen- and oxygen-doped fuel cell catalysts by thermal decomposition of nitrogen- and oxygen-containing organic matter, the preparation method of the first aspect of the embodiment of the present invention performs the nitrogen doping step and the oxygen doping step separately, thereby avoiding the mutual antagonism between the anchoring effect of nitrogen doping on the active components and the promoting effect of oxygen doping on the intrapore loading, and can give full play to the effect of the two doping elements on improving the catalytic activity and durability of the catalyst.

[0020] A second aspect of an embodiment of the present invention provides a method for preparing a fuel cell catalyst, comprising the following steps:

[0021] S201, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier;

[0022] S202, subjecting the oxidized carbon support to a second sintering treatment in an ammonia atmosphere to obtain an ammonolyzed carbon support;

[0023] S203, loading active metals onto the carbon carrier after the ammonolysis to obtain the fuel cell catalyst.

[0024] The advantages and technical effects brought by the preparation method of the second aspect of the embodiment of the present invention are:

[0025] 1. Compared with the fuel cell catalyst preparation method that only performs nitrogen doping or only performs oxygen doping, the preparation method of the second aspect of the embodiment of the present invention adopts a treatment method that combines oxygen atmosphere oxidation treatment and ammonia atmosphere ammonia decomposition treatment to regulate the preparation of nitrogen and oxygen-doped carbon materials, thereby improving the dispersion uniformity and intrapore loading ratio of the active metal using the carbon material as a carrier, and also improving the dispersion uniformity of the resin on the catalyst surface during the subsequent preparation of the catalyst layer, thereby improving the catalytic performance of the catalyst layer.

[0026] 2. The fuel cell catalyst preparation methods of the related art that only carry out nitrogen doping or only carry out oxygen doping can achieve a low doping content of heteroatoms (nitrogen or oxygen) in the carbon material, while the preparation method of the second aspect of the embodiment of the present invention can greatly increase the doping content of heteroatoms (nitrogen and oxygen) in the carbon material, which is more conducive to improving the catalytic activity and durability of the catalyst.

[0027] 3. The preparation method of the second aspect of the embodiment of the present invention can prepare a supported catalyst with a higher loading capacity. By loading the active metal on the nitrogen- and oxygen-doped carbon carrier, the in-pore loading ratio of the catalyst is increased, and the active metal can be anchored at the nitrogen-containing sites, thereby ensuring the active metal dispersion of the higher loading catalyst.

[0028] 4. The preparation method of the second aspect of the embodiment of the present invention adopts air oxidation instead of oxidation by hazardous oxides such as concentrated nitric acid oxidation, thereby increasing the oxygen-containing functional groups and oxygen atom doping numbers on the surface of the carbon carrier after oxidation as reaction sites for the nitrogen doping process by ammonolysis treatment, significantly improving the efficiency of nitrogen doping by ammonolysis treatment, greatly reducing the difficulty of nitrogen doping of the carrier, and significantly improving the efficiency of nitrogen doping by ammonolysis treatment through a low-cost, low-risk method, and also providing a mass production approach for nitrogen doping of carbon materials or other materials.

[0029] 5. Compared with the method of preparing nitrogen- and oxygen-doped fuel cell catalysts by thermal decomposition of nitrogen- and oxygen-containing organic matter, the preparation method of the second aspect of the embodiment of the present invention performs the nitrogen doping step and the oxygen doping step separately, thereby avoiding the mutual antagonism between the anchoring effect of nitrogen doping on the active components and the promoting effect of oxygen doping on the intrapore loading, and can give full play to the effect of the two doping elements on improving the catalytic activity and durability of the catalyst.

[0030] A third aspect of an embodiment of the present invention provides a method for preparing a fuel cell catalyst, comprising the following steps:

[0031] S301, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier;

[0032] S302, loading an active metal onto the oxidized carbon support to obtain a first catalyst;

[0033] S303, performing a second sintering treatment on the first catalyst in an ammonia atmosphere to obtain the fuel cell catalyst.

[0034] The advantages and technical effects brought by the preparation method of the third aspect of the embodiment of the present invention are:

[0035] 1. Compared with the fuel cell catalyst preparation method that only performs nitrogen doping or only performs oxygen doping, the preparation method of the third aspect of the embodiment of the present invention adopts a treatment method that combines oxygen atmosphere oxidation treatment and ammonia atmosphere ammonia decomposition treatment to regulate the preparation of nitrogen and oxygen-doped carbon materials, thereby improving the dispersion uniformity and intrapore loading ratio of the active metal using the carbon material as a carrier, and also improving the dispersion uniformity of the resin on the catalyst surface during the subsequent preparation of the catalyst layer, thereby improving the catalytic performance of the catalyst layer.

[0036] 2. The fuel cell catalyst preparation methods of the related art that only carry out nitrogen doping or only carry out oxygen doping can achieve a low doping content of heteroatoms (nitrogen or oxygen) in the carbon material, while the preparation method of the third aspect of the embodiment of the present invention can greatly increase the doping content of heteroatoms (nitrogen and oxygen) in the carbon material, which is more conducive to improving the catalytic activity and durability of the catalyst.

[0037] 3. The preparation method of the third aspect of the embodiment of the present invention increases the in-pore loading ratio of the catalyst by loading the active metal on the carrier with high oxygen functional groups. After the material is ammonolyzed, the active metal will also be anchored at the nitrogen-containing sites, ensuring the active metal dispersion of the catalyst with a higher loading amount.

[0038] 4. The preparation method of the third aspect of the embodiment of the present invention adopts air oxidation instead of concentrated nitric acid oxidation, which increases the oxygen-containing functional groups and oxygen atom doping on the surface of the carbon carrier after oxidation as reaction sites for the nitrogen doping process of ammonolysis treatment, significantly improves the efficiency of nitrogen doping by ammonolysis treatment, and greatly reduces the difficulty of nitrogen doping of the carrier. This method is a mass production approach to achieve controllable nitrogen doping of carbon carriers.

[0039] 5. Compared with the method of preparing nitrogen- and oxygen-doped fuel cell catalysts by thermal decomposition of nitrogen- and oxygen-containing organic matter, the preparation method of the third aspect of the embodiment of the present invention performs the nitrogen doping step and the oxygen doping step separately, thereby avoiding the mutual antagonism between the anchoring effect of nitrogen doping on the active components and the promoting effect of oxygen doping on the intrapore loading, and can give full play to the effect of the two doping elements on improving the catalytic activity and durability of the catalyst.

[0040] A fourth aspect of the embodiments of the present invention provides a fuel cell catalyst obtained by the preparation method of the first aspect, the second aspect or the third aspect.

[0041] The advantages and technical effects brought by the fuel cell catalyst of the fourth aspect of the embodiment of the present invention are:

[0042] The catalyst obtained by the preparation method of the first aspect, the second aspect or the third aspect of the embodiment of the present invention has the characteristics of high dispersion, high loading, high nitrogen and oxygen doping ratios, high intrapore loading and mass production. When used in fuel cells, it can improve the dispersion of the resin and reduce the poisoning effect of the sulfonic acid group, so that the catalyst has the characteristics of high activity and long life.

[0043] A fifth aspect of the embodiments of the present invention provides a fuel cell comprising the fuel cell catalyst of the fourth aspect.

[0044] The advantages and technical effects brought by the fuel cell of the fifth aspect of the embodiment of the present invention are as follows:

[0045] Since the fuel cell catalyst of the fourth aspect of the embodiment of the present invention is used, the fuel cell of the fifth aspect of the embodiment of the present invention has high efficiency and stable operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a linear sweep voltage-current curve of the finished catalyst of Comparative Example 4 and the finished catalyst of Example 1 in the oxygen reduction rotating disk electrode test.

[0047] Figure 2 It is a curve of the decay percentage of the electrochemical active area relative to the initial value of the cycle number in the three-electrode system electrochemical square wave endurance test using the finished catalyst of Comparative Example 4 and the finished catalyst of Example 1. DETAILED DESCRIPTION

[0048] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0049] A first aspect of an embodiment of the present invention provides a method for preparing a fuel cell catalyst, comprising the following steps:

[0050] S101, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier;

[0051] S102, loading a first active metal on the oxidized carbon support to obtain a first catalyst;

[0052] S103, performing a second sintering treatment on the first catalyst in an ammonia atmosphere to obtain a second catalyst;

[0053] S104, loading a second active metal onto the second catalyst to obtain the fuel cell catalyst.

[0054] Compared with the fuel cell catalyst preparation method that only performs nitrogen doping or only performs oxygen doping, the preparation method of the first aspect of the embodiment of the present invention adopts a treatment method that combines oxygen atmosphere oxidation treatment and ammonia atmosphere ammonia decomposition treatment to regulate the preparation of nitrogen and oxygen-doped carbon materials, thereby improving the dispersion uniformity and intrapore loading ratio of the active metal using the carbon material as a carrier, and also improving the dispersion uniformity of the resin on the catalyst surface during the subsequent preparation of the catalyst layer, thereby improving the catalytic performance of the catalyst layer.

[0055] The fuel cell catalyst preparation methods of the related art that only perform nitrogen doping or only perform oxygen doping can achieve a low doping content of heteroatoms (nitrogen or oxygen) in the carbon material, while the preparation method of the first aspect of the embodiment of the present invention can greatly increase the doping content of heteroatoms (nitrogen and oxygen) in the carbon material, which is more conducive to improving the catalytic activity and durability of the catalyst.

[0056] The preparation method of the first aspect of the embodiment of the present invention adopts air oxidation instead of concentrated nitric acid oxidation, which increases the oxygen-containing functional groups and oxygen atom doping numbers on the surface of the carbon carrier after oxidation as reaction sites for the nitrogen doping process by ammonolysis treatment, significantly improves the efficiency of nitrogen doping by ammonolysis treatment, and greatly reduces the difficulty of nitrogen doping of the carrier. This method is a mass production approach to achieve controllable nitrogen doping of carbon carriers.

[0057] The preparation method of the first aspect of the embodiment of the present invention utilizes a step-by-step loading method. First, oxygen atoms are doped into the inner and outer surfaces of the carbon carrier through step S101, so that the oxidized carbon carrier has a high oxygen content. Secondly, a certain proportion of active metals are loaded on the oxidized carbon carrier through step S102. On the one hand, compared with the method without step S101, the preparation method of the first aspect of the embodiment of the present invention significantly increases the intrapore loading ratio of active metals; on the other hand, compared with loading all active metals at once through step S102, the low loading of active metals in step S102 of the preparation method of the first aspect of the present invention reduces the process risk of flammability of the first catalyst with high oxygen content during the preparation process. Then, the first catalyst is subjected to ammonia decomposition treatment through step S103, and while regulating and reducing the oxygen content on the surface of the first catalyst, nitrogen atoms are doped into the inner and outer surfaces of the first catalyst to obtain a second catalyst; finally, the second catalyst is loaded with active metals for the second time through step S104, and a nitrogen and oxygen-doped high active metal loading, high dispersion, and high intrapore loading supported catalyst is obtained, that is, the fuel cell catalyst provided by the embodiment of the present invention.

[0058] Compared with the method of preparing nitrogen and oxygen-doped fuel cell catalysts by thermal decomposition of nitrogen-oxygen-containing organic matter, the preparation method of the first aspect of the embodiment of the present invention performs the nitrogen doping step and the oxygen doping step separately, avoiding the mutual antagonism between the anchoring effect of nitrogen doping on the active components and the promoting effect of oxygen doping on the intrapore loading, and can give full play to the effect of the two doping elements on improving the catalytic activity and durability of the catalyst.

[0059] The preparation method of the first aspect of the embodiment of the present invention has no particular restrictions on the carbon material, as long as it can be used as a carbon material for a fuel cell catalyst carrier, for example, it may include but is not limited to at least one of carbon black, graphitized carbon, graphite, carbon nanotubes, graphene and a material with a carbon coating layer.

[0060] In some embodiments, in step S101, the volume percentage of oxygen in the oxygen atmosphere is 1% to 100%, for example, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc. Preferably, the volume percentage of oxygen in the oxygen atmosphere is 10% to 100%, which is conducive to increasing the amount of oxygen-containing functional groups and oxygen atom doping on the surface of the oxidized carbon carrier.

[0061] For example, the oxygen atmosphere may be air, or a mixture of air and / or oxygen and an inert gas, wherein the inert gas may be nitrogen and / or argon, etc. If the oxygen atmosphere is a mixture of oxygen and an inert gas, the oxygen content in the oxygen atmosphere may be regulated by regulating the flow rate ratio of oxygen and the inert gas. It is preferred to use air as the oxygen atmosphere for sintering to reduce the gas cost during mass production, because when other proportions of gas distribution are used, it is necessary to prepare it by mixing air and / or oxygen with an inert gas, which increases the cost of the oxygen atmosphere.

[0062] The preparation method of the first aspect of the embodiment of the present invention has no particular restrictions on the atmosphere sintering equipment used in step S101, as long as the first sintering process can be completed. For example, the atmosphere sintering equipment may include but is not limited to equipment with atmosphere sintering function such as a tubular furnace, a vacuum furnace, an atmosphere furnace, and a muffle furnace, and the sintering carrier may be made of a material that does not react with oxygen atmosphere and carbon material at high temperature.

[0063] In some embodiments, in step S101, the holding temperature of the first sintering treatment is 200°C to 800°C, such as 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, etc.; the holding time of the first sintering treatment is 0.5 hours to 12 hours, such as 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc. In the oxidation process of batch carbon materials, the holding temperature of the first sintering treatment is further preferably 500°C to 700°C, and the holding time of the first sintering treatment is preferably 1 hour to 5 hours. When the holding temperature of the first sintering treatment is too low, it is not conducive to increasing the oxygen doping ratio of the oxidized carbon material, and the holding time of the first sintering treatment is prolonged, reducing production efficiency. When the holding temperature of the first sintering treatment is too high, the carbon material is lost more due to oxidation, and the production cost increases.

[0064] In some embodiments, in step S103, the volume percentage of ammonia in the ammonia atmosphere is 1% to 100%, such as 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc. When the proportion of ammonia in the ammonia atmosphere is lower than 1%, it is necessary to increase the insulation temperature of the second sintering treatment, which may be accompanied by agglomeration of the active metal of the catalyst. Preferably, the volume percentage of ammonia in the ammonia atmosphere is 10% to 100%, which is conducive to increasing the number of nitrogen-containing functional groups and nitrogen atoms doped on the surface of the second catalyst.

[0065] For example, the ammonia atmosphere can be ammonia or a mixture of ammonia and an inert gas, wherein the inert gas can be nitrogen and / or argon. If the latter, the ammonia ratio in the ammonia atmosphere can be regulated by adjusting the flow rate ratio of ammonia and the inert gas. When preparing a small-grain catalyst with high catalytic activity as the goal, it is preferred to use pure ammonia as the ammonia atmosphere for sintering to reduce the insulation temperature of the second sintering treatment and avoid agglomeration of active metals.

[0066] The preparation method of the first aspect of the embodiment of the present invention has no particular restrictions on the atmosphere sintering equipment used in step S103, as long as the second sintering process can be completed. For example, the atmosphere sintering equipment may include but is not limited to equipment with atmosphere sintering function such as a tubular furnace, a vacuum furnace, an atmosphere furnace, and a muffle furnace, and the sintering carrier may be made of a material that does not react with the ammonia atmosphere and the first catalyst at high temperature.

[0067] In some embodiments, in step S103, the insulation temperature of the second sintering treatment is 100°C to 1000°C, such as 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, etc.; the insulation time of the second sintering treatment is 0.5 hours to 12 hours, such as 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc. In the ammonolysis process of batch materials, the insulation temperature of the second sintering treatment is further preferably 200 to 400°C, and the insulation time of the second sintering treatment is preferably 1 hour to 5 hours. When the ammonolysis temperature is too low, the nitrogen doping ratio of the material is too low, the ammonolysis time is extended, and the production efficiency is reduced. When the ammonolysis temperature is too high, the active metals on the catalyst may agglomerate, which is not conducive to improving the catalytic activity of the finished catalyst.

[0068] The preparation method of the first aspect of the embodiment of the present invention has no particular restrictions on the type of the first active metal supported in step S102, and can be any active metal single substance or alloy in the related art. For example, the first active metal can include but is not limited to at least one of platinum, ruthenium, iridium, gold, cobalt, iron, nickel, copper, cerium, manganese, palladium and silver.

[0069] The preparation method of the first aspect of the embodiment of the present invention has no particular restrictions on the type of the second active metal supported in step S104, and can be any active metal single substance or alloy in the related art. For example, the second active metal can include but is not limited to at least one of platinum, ruthenium, iridium, gold, cobalt, iron, nickel, copper, cerium, manganese, palladium and silver.

[0070] In the preparation method of the first aspect of the embodiment of the present invention, the first active metal supported in step S102 and the second active metal supported in step S104 can be of the same type or of different types. If it is the latter, the preparation process can prepare alloy catalysts and multifunctional catalysts.

[0071] In some embodiments, based on the total mass of the fuel cell catalyst as 100%, the sum of the mass percentages of the first active metal in step S102 and the second active metal in step S104 is greater than 0 and less than or equal to 80%, such as 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, etc. When the total loading of the active metal is too low, it is not conducive to improving the catalytic activity of the catalyst. When the total loading of the active metal is too high, it is not conducive to improving the uniformity of the active metal dispersion, thereby not being conducive to improving the durability of the catalyst.

[0072] In some embodiments, the mass ratio of the first active metal in step S102 to the second active metal in step S104 is (0.1-10):1, such as 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc. Since the oxidized carbon carrier has a high oxygen content, compared with the method in which the loading amount of the first active metal is greater than or equal to the loading amount of the second active metal, the method in which the loading amount of the first active metal is less than the loading amount of the second active metal can ensure the low loading amount of active metal in step S102, thereby reducing the process risk of the first catalyst with a high oxygen content in step S102 being flammable during the preparation process.

[0073] The preparation method of the first aspect of the embodiment of the present invention has no particular restrictions on the method for achieving the first active metal loading in step S102, and can be any active metal loading method in the related art. For example, a certain proportion of the first active metal precursor can be loaded on the oxidized carbon carrier by a loading method such as liquid phase reduction method, vacuum impregnation method, equal volume impregnation method, etc., and then after drying, sintering, etc., the first active metal is loaded to obtain the first catalyst.

[0074] For example, in step S102, the first active metal can be loaded by a liquid phase reduction method. Specifically, the first active metal salt is used as a precursor, and the first active metal salt is prepared into a solution as a precursor solution to impregnate the oxidized carbon material. The impregnated oxidized carbon material is then dried and sintered to complete the loading of the first active metal, thereby obtaining a first catalyst.

[0075] Optionally, the first active metal salt may include but is not limited to at least one of platinum salts, ruthenium salts, iridium salts, gold salts, cobalt salts, iron salts, nickel salts, copper salts, cerium salts, manganese salts, palladium salts and silver salts. Wherein, the platinum salt may be selected from at least one of chloroplatinic acid, platinum nitrate, tetraammine platinum nitrate, platinum acetylacetonate and platinum phthalocyanine. The platinum salt may preferably be platinum acetylacetonate and / or platinum phthalocyanine. Wherein, the ruthenium salt may be selected from ruthenium chloride and / or ruthenium acetylacetonate. Wherein, the iridium salt may be selected from at least one of iridium chloride, iridium acetylacetonate and chloroiridic acid. Wherein, the cobalt salt may be selected from at least one of cobalt nitrate, cobalt acetate, cobalt chloride and cobalt acetylacetonate. Wherein, the iron salt may be selected from at least one of ferric nitrate, ferric chloride, ferric acetylacetonate and ferric citrate. Wherein, the nickel salt may be selected from at least one of nickel acetylacetonate, nickel nitrate and nickel dichloride. Other types of first active metal salts are no longer listed one by one.

[0076] Optionally, in step S102, the mass ratio of the oxidized carbon carrier to the metal element in the first active metal salt is 2:3 to 100:1, and the volume ratio of the first active metal salt solution to the saturated impregnation volume of the oxidized carbon carrier may be 0.1:1 to 10:1.

[0077] The preparation method of the first aspect of the embodiment of the present invention has no particular restrictions on the method for achieving the second active metal loading in step S104, and can be any active metal loading method in the related art. For example, a certain proportion of the second active metal precursor can be loaded on the oxidized carbon carrier by a loading method such as liquid phase reduction method, vacuum impregnation method, equal volume impregnation method, etc., and then after drying, sintering, etc., the second active metal is loaded, thereby obtaining the final fuel cell catalyst.

[0078] For example, in step S104, the second active metal can be loaded by liquid phase reduction method. Specifically, the second active metal salt is used as a precursor, and the second active metal salt is prepared into a solution as a precursor solution to impregnate the second catalyst, and then the impregnated second catalyst is dried and sintered to complete the loading of the second active metal, thereby obtaining the final fuel cell catalyst. The second active metal salt may include but is not limited to at least one of platinum salts, ruthenium salts, iridium salts, gold salts, cobalt salts, iron salts, nickel salts, copper salts, cerium salts, manganese salts, palladium salts and silver salts. Among them, the platinum salt can be selected from at least one of chloroplatinic acid, platinum nitrate, tetraammine platinum nitrate, acetylacetonate platinum and phthalocyanine platinum. The platinum salt can preferably be acetylacetonate platinum and / or phthalocyanine platinum. Among them, the ruthenium salt can be selected from ruthenium chloride and / or acetylacetonate ruthenium. Among them, the iridium salt can be selected from at least one of iridium chloride, acetylacetonate iridium and chloroiridic acid. Among them, the cobalt salt can be selected from at least one of cobalt nitrate, cobalt acetate, cobalt chloride and acetylacetonate cobalt. Wherein, the iron salt can be selected from at least one of ferric nitrate, ferric chloride, ferric acetylacetonate and ferric citrate. Wherein, the nickel salt can be selected from at least one of nickel acetylacetonate, nickel nitrate and nickel dichloride. Other types of second active metal salts are not listed one by one.

[0079] Optionally, in step S104, the mass ratio of the second catalyst to the metal element in the second active metal salt is 2:3 to 100:1, and the volume ratio of the second active metal salt solution to the saturated impregnation volume of the second catalyst may be 0.1:1 to 2:1.

[0080] A second aspect of an embodiment of the present invention provides a method for preparing a fuel cell catalyst, comprising the following steps:

[0081] S201, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier;

[0082] S202, subjecting the oxidized carbon support to a second sintering treatment in an ammonia atmosphere to obtain an ammonolyzed carbon support;

[0083] S203, loading active metals onto the carbon carrier after the ammonolysis to obtain the fuel cell catalyst.

[0084] Compared with the fuel cell catalyst preparation method that only performs nitrogen doping or only performs oxygen doping, the preparation method of the second aspect of the embodiment of the present invention adopts a treatment method that combines oxygen atmosphere oxidation treatment and ammonia atmosphere ammonia decomposition treatment to regulate the preparation of nitrogen and oxygen-doped carbon materials, thereby improving the dispersion uniformity and intrapore loading ratio of the active metal using the carbon material as a carrier, and also improving the dispersion uniformity of the resin on the catalyst surface during the subsequent preparation of the catalyst layer, thereby improving the catalytic performance of the catalyst layer.

[0085] The fuel cell catalyst preparation methods of the related art that only perform nitrogen doping or only perform oxygen doping can achieve a low doping content of heteroatoms (nitrogen or oxygen) in the carbon material, while the preparation method of the second aspect of the embodiment of the present invention can greatly increase the doping content of heteroatoms (nitrogen and oxygen) in the carbon material, which is more conducive to improving the catalytic activity and durability of the catalyst.

[0086] The preparation method of the second aspect of the embodiment of the present invention adopts air oxidation instead of concentrated nitric acid oxidation, which increases the oxygen-containing functional groups and oxygen atom doping number on the surface of the carbon carrier after oxidation as reaction sites for the ammonolysis treatment and nitrogen doping process, significantly improves the efficiency of the ammonolysis treatment and nitrogen doping, and greatly reduces the difficulty of nitrogen doping of the carrier. This method is a mass production approach to achieve controllable nitrogen doping of carbon carriers.

[0087] Compared with the method of preparing nitrogen and oxygen-doped fuel cell catalysts by thermal decomposition of nitrogen-oxygen-containing organic matter, the preparation method of the second aspect of the embodiment of the present invention performs the nitrogen doping step and the oxygen doping step separately, avoiding the mutual antagonism between the anchoring effect of nitrogen doping on the active components and the promoting effect of oxygen doping on the intrapore loading, and can give full play to the effect of the two doping elements on improving the catalytic activity and durability of the catalyst.

[0088] The difference between the preparation method of the second aspect of the embodiment of the present invention and the preparation method of the first aspect mainly lies in that a one-time active metal loading method is adopted, and the step of loading the active metal is located after the ammonolysis treatment. The preparation method of the second aspect of the embodiment of the present invention firstly dopes oxygen atoms into the inner and outer surfaces of the carbon carrier through step S201, so that the oxidized carbon carrier has a high oxygen content. Then, the oxidized carbon carrier gas is subjected to ammonolysis treatment through step S202, and while regulating and reducing the oxygen content on the surface of the oxidized carbon carrier, nitrogen atoms are doped into the inner and outer surfaces of the oxidized carbon carrier to obtain the carbon carrier after ammonolysis. Finally, step S203 is used to load the secondary active metal on the carbon carrier after ammonolysis, and a nitrogen and oxygen-doped supported catalyst with high active metal loading, high dispersion, and high intrapore loading is obtained, that is, the fuel cell catalyst provided by the embodiment of the present invention.

[0089] The preparation method of the second aspect of the embodiment of the present invention has no particular restrictions on the carbon material, as long as it can be used as a carbon material for a fuel cell catalyst carrier, for example, it can include but is not limited to at least one of carbon black, graphitized carbon, graphite, carbon nanotubes, graphene and materials with a carbon coating layer. The above carbon materials can be prepared by pyrolysis, carbonization and other methods.

[0090] In some embodiments, in step S201, the volume percentage of oxygen in the oxygen atmosphere is 1% to 100%, for example, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc. Preferably, the volume percentage of oxygen in the oxygen atmosphere is 10% to 100%, which is conducive to increasing the amount of oxygen-containing functional groups and oxygen atom doping on the surface of the oxidized carbon carrier.

[0091] For example, the oxygen atmosphere may be air, or a mixture of air and / or oxygen and an inert gas, wherein the inert gas may be nitrogen and / or argon, etc. If the oxygen atmosphere is a mixture of oxygen and an inert gas, the oxygen content in the oxygen atmosphere may be regulated by regulating the flow rate ratio of oxygen and the inert gas. It is preferred to use air as the oxygen atmosphere for sintering to reduce the gas cost during mass production, because when other proportions of gas distribution are used, it is necessary to prepare it by mixing air and / or oxygen with an inert gas, which increases the cost of the oxygen atmosphere.

[0092] The preparation method of the second aspect of the embodiment of the present invention has no particular restrictions on the atmosphere sintering equipment used in step S201, as long as the first sintering process can be completed. For example, the atmosphere sintering equipment may include but is not limited to equipment with atmosphere sintering functions such as a tubular furnace, a vacuum furnace, an atmosphere furnace, and a muffle furnace, and the sintering carrier may be made of a material that does not react with oxygen atmosphere and carbon materials at high temperatures.

[0093] In some embodiments, in step S201, the holding temperature of the first sintering treatment is 200°C to 800°C, such as 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, etc.; the holding time of the first sintering treatment is 0.5 hours to 12 hours, such as 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc. In the oxidation process of batch carbon materials, the holding temperature of the first sintering treatment is further preferably 500°C to 700°C, and the holding time of the first sintering treatment is preferably 1 hour to 5 hours. When the holding temperature of the first sintering treatment is too low, it is not conducive to increasing the oxygen doping ratio of the oxidized carbon material, and the holding time of the first sintering treatment is prolonged, reducing production efficiency. When the holding temperature of the first sintering treatment is too high, the carbon material is lost more due to oxidation, and the production cost increases.

[0094] In some embodiments, in step S202, the volume percentage of ammonia in the ammonia atmosphere is 1% to 100%, for example, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc. When the proportion of ammonia in the ammonia atmosphere is lower than 1%, it is necessary to increase the insulation temperature of the second sintering treatment, which may be accompanied by agglomeration of the active metal of the catalyst. Preferably, the volume percentage of ammonia in the ammonia atmosphere is 10% to 100%, which is conducive to increasing the number of nitrogen-containing functional groups and nitrogen atoms doped on the surface of the carbon carrier after ammonia decomposition.

[0095] For example, the ammonia atmosphere can be ammonia or a mixture of ammonia and an inert gas, wherein the inert gas can be nitrogen and / or argon. If the latter, the ammonia ratio in the ammonia atmosphere can be regulated by adjusting the flow rate ratio of ammonia and the inert gas. When preparing a small-grain catalyst with high catalytic activity as the goal, it is preferred to use pure ammonia as the ammonia atmosphere for sintering to reduce the insulation temperature of the second sintering treatment and avoid agglomeration of active metals.

[0096] The preparation method of the second aspect of the embodiment of the present invention has no particular restrictions on the atmosphere sintering equipment used in step S202, as long as the second sintering process can be completed. For example, the atmosphere sintering equipment may include but is not limited to equipment with atmosphere sintering function such as a tubular furnace, a vacuum furnace, an atmosphere furnace, and a muffle furnace, and the sintering carrier may be made of a material that does not react with the ammonia atmosphere and the oxidized carbon carrier at high temperature.

[0097] In some embodiments, in step S202, the insulation temperature of the second sintering treatment is 100°C to 1000°C, such as 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, etc.; the insulation time of the second sintering treatment is 0.5 hours to 12 hours, such as 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc. In the ammonolysis process of batch materials, the insulation temperature of the second sintering treatment is further preferably 200 to 400°C, and the insulation time of the second sintering treatment is preferably 1 hour to 5 hours. When the ammonolysis temperature is too low, the nitrogen doping ratio of the material is too low, the ammonolysis time is extended, and the production efficiency is reduced. When the ammonolysis temperature is too high, the active metals on the catalyst may agglomerate, which is not conducive to improving the catalytic activity of the finished catalyst.

[0098] The preparation method of the second aspect of the embodiment of the present invention has no particular restrictions on the type of active metal supported in step S203, and can be any active metal single substance or alloy in the related art. For example, the active metal can include but is not limited to at least one of platinum, ruthenium, iridium, gold, cobalt, iron, nickel, copper, cerium, manganese, palladium and silver.

[0099] In some embodiments, based on the total mass of the fuel cell catalyst as 100%, the mass percentage of the active metal is greater than 0 and less than or equal to 80%, such as 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, etc. When the loading of the active metal is too low, it is not conducive to improving the catalytic activity of the catalyst. When the loading of the active metal is too high, it is not conducive to improving the uniformity of the active metal dispersion, thereby not being conducive to improving the durability of the catalyst.

[0100] The preparation method of the second aspect of the embodiment of the present invention has no particular restrictions on the method for achieving active metal loading in step S203, and can be any active metal loading method in the related art. For example, a loading method such as a liquid phase reduction method, a vacuum impregnation method, an equal volume impregnation method, etc. can be used to load the active metal precursor on the carbon carrier after aminolysis, and then after drying, sintering, etc., the active metal is loaded to obtain the final fuel cell catalyst.

[0101] For example, in step S203, the active metal can be loaded by liquid phase reduction method. Specifically, the active metal salt is used as a precursor, and the active metal salt is prepared into a solution as a precursor solution to impregnate the carbon material after ammonolysis. The impregnated carbon material after ammonolysis is then dried and sintered to complete the loading of the active metal, thereby obtaining the final fuel cell catalyst.

[0102] Optionally, the active metal salt may include but is not limited to at least one of platinum salts, ruthenium salts, iridium salts, gold salts, cobalt salts, iron salts, nickel salts, copper salts, cerium salts, manganese salts, palladium salts and silver salts. Wherein, the platinum salt may be selected from at least one of chloroplatinic acid, platinum nitrate, tetraammine platinum nitrate, platinum acetylacetonate and platinum phthalocyanine. The platinum salt may preferably be platinum acetylacetonate and / or platinum phthalocyanine. Wherein, the ruthenium salt may be selected from ruthenium chloride and / or ruthenium acetylacetonate. Wherein, the iridium salt may be selected from at least one of iridium chloride, iridium acetylacetonate and chloroiridic acid. Wherein, the cobalt salt may be selected from at least one of cobalt nitrate, cobalt acetate, cobalt chloride and cobalt acetylacetonate. Wherein, the iron salt may be selected from at least one of ferric nitrate, ferric chloride, ferric acetylacetonate and ferric citrate. Wherein, the nickel salt may be selected from at least one of nickel acetylacetonate, nickel nitrate and nickel dichloride. Other types of active metal salts are not listed one by one.

[0103] Optionally, the mass ratio of the carbon support after ammonolysis to the metal element in the active metal salt is 2:3 to 100:1, and the volume ratio of the active metal salt solution to the saturated impregnation volume of the carbon support after ammonolysis can be 0.1:1 to 2:1.

[0104] A third aspect of an embodiment of the present invention provides a method for preparing a fuel cell catalyst, comprising the following steps:

[0105] S301, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier;

[0106] S302, loading an active metal onto the oxidized carbon support to obtain a first catalyst;

[0107] S303, performing a second sintering treatment on the first catalyst in an ammonia atmosphere to obtain the fuel cell catalyst.

[0108] Compared with the fuel cell catalyst preparation method that only performs nitrogen doping or only performs oxygen doping, the preparation method of the third aspect of the embodiment of the present invention adopts a treatment method that combines oxygen atmosphere oxidation treatment and ammonia atmosphere ammonia decomposition treatment to regulate the preparation of nitrogen and oxygen-doped carbon materials, thereby improving the dispersion uniformity and intrapore loading ratio of the active metal using the carbon material as a carrier, and also improving the dispersion uniformity of the resin on the catalyst surface during the subsequent preparation of the catalyst layer, thereby improving the catalytic performance of the catalyst layer.

[0109] The fuel cell catalyst preparation methods of the related art that only perform nitrogen doping or only perform oxygen doping can achieve a low doping content of heteroatoms (nitrogen or oxygen) in the carbon material, while the preparation method of the third aspect of the embodiment of the present invention can greatly increase the doping content of heteroatoms (nitrogen and oxygen) in the carbon material, which is more conducive to improving the catalytic activity and durability of the catalyst.

[0110] The preparation method of the third aspect of the embodiment of the present invention adopts air oxidation instead of concentrated nitric acid oxidation, which increases the oxygen-containing functional groups and the number of oxygen atoms doped on the surface of the carbon carrier after oxidation as reaction sites for the nitrogen doping process of the ammonolysis treatment, significantly improves the efficiency of the nitrogen doping process of the ammonolysis treatment, and greatly reduces the difficulty of nitrogen doping of the carrier. This method is a mass production approach to achieve controllable nitrogen doping of carbon carriers.

[0111] Compared with the method of preparing nitrogen and oxygen-doped fuel cell catalysts by thermal decomposition of nitrogen-oxygen-containing organic matter, the preparation method of the third aspect of the embodiment of the present invention performs the nitrogen doping step and the oxygen doping step separately, avoiding the mutual antagonism between the anchoring effect of nitrogen doping on the active components and the promoting effect of oxygen doping on the intrapore loading, and can give full play to the effect of the two doping elements on improving the catalytic activity and durability of the catalyst.

[0112] The difference between the preparation method of the third aspect of the embodiment of the present invention and the preparation method of the first aspect is that a one-time active metal loading method is adopted, and the step of loading the active metal is located between the oxidation treatment and the ammonolysis treatment. The preparation method of the third aspect of the embodiment of the present invention first dopes oxygen atoms into the inner and outer surfaces of the carbon carrier through step S301, so that the oxidized carbon carrier has a high oxygen content. Secondly, the active metal is loaded on the oxidized carbon carrier through step S302. On the one hand, compared with the method without step S301, the preparation method of the third aspect of the embodiment of the present invention significantly increases the intrapore loading ratio of the active metal. Then, the first catalyst is subjected to ammonolysis treatment through step S303, and while regulating and reducing the oxygen content on the surface of the first catalyst, nitrogen atoms are doped into the inner and outer surfaces of the first catalyst to obtain a nitrogen and oxygen-doped high active metal loading, high dispersion, and high intrapore loading supported catalyst, that is, the fuel cell catalyst provided by the embodiment of the present invention. It should be noted that although the ammoniation treatment in the preparation method of the third aspect of the embodiment of the present invention is located after the active metal loading, it does not improve the active metal loading compared to the preparation methods of the first and second aspects, but the ammoniation treatment is still beneficial to the uniform dispersion of the resin in the subsequent preparation of the catalytic layer.

[0113] The preparation method of the third aspect of the embodiment of the present invention has no particular restrictions on the carbon material, as long as it can be used as a carbon material that can be used as a fuel cell catalyst carrier, for example, it may include but is not limited to at least one of carbon black, graphitized carbon, graphite, carbon nanotubes, graphene, carbon materials prepared by pyrolysis, carbonization, etc., and materials with a carbon coating layer.

[0114] In some embodiments, in step S301, the volume percentage of oxygen in the oxygen atmosphere is 1% to 100%, for example, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc. Preferably, the volume percentage of oxygen in the oxygen atmosphere is 10% to 100%, which is conducive to increasing the amount of oxygen-containing functional groups and oxygen atom doping on the surface of the oxidized carbon carrier.

[0115] For example, the oxygen atmosphere may be air, or a mixture of air and / or oxygen and an inert gas, wherein the inert gas may be nitrogen and / or argon, etc. If the oxygen atmosphere is a mixture of oxygen and an inert gas, the oxygen content in the oxygen atmosphere may be regulated by regulating the flow rate ratio of oxygen and the inert gas. It is preferred to use air as the oxygen atmosphere for sintering to reduce the gas cost during mass production, because when other proportions of gas distribution are used, it is necessary to prepare it by mixing air and / or oxygen with an inert gas, which increases the cost of the oxygen atmosphere.

[0116] The preparation method of the third aspect of the embodiment of the present invention has no particular restrictions on the atmosphere sintering equipment used in step S301, as long as the first sintering process can be completed. For example, the atmosphere sintering equipment may include but is not limited to equipment with atmosphere sintering function such as a tubular furnace, a vacuum furnace, an atmosphere furnace, and a muffle furnace, and the sintering carrier may be made of a material that does not react with oxygen atmosphere and carbon material at high temperature.

[0117] In some embodiments, in step S301, the holding temperature of the first sintering treatment is 200°C to 800°C, such as 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, etc.; the holding time of the first sintering treatment is 0.5 hours to 12 hours, such as 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc. In the oxidation process of batch carbon materials, the holding temperature of the first sintering treatment is further preferably 500°C to 700°C, and the holding time of the first sintering treatment is preferably 1 hour to 5 hours. When the holding temperature of the first sintering treatment is too low, it is not conducive to increasing the oxygen doping ratio of the oxidized carbon material, and the holding time of the first sintering treatment is prolonged, reducing production efficiency. When the holding temperature of the first sintering treatment is too high, the carbon material is lost more due to oxidation, and the production cost increases.

[0118] The preparation method of the third aspect of the embodiment of the present invention has no particular restrictions on the type of active metal supported in step S302, and can be any active metal single substance or alloy in the related art. For example, the active metal can include but is not limited to at least one of platinum, ruthenium, iridium, gold, cobalt, iron, nickel, copper, cerium, manganese, palladium and silver.

[0119] In some embodiments, based on the total mass of the fuel cell catalyst as 100%, the mass percentage of the active metal is greater than 0 and less than or equal to 80%, such as 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, etc. When the loading of the active metal is too low, it is not conducive to improving the catalytic activity of the catalyst. When the loading of the active metal is too high, it is not conducive to improving the uniformity of the active metal dispersion, thereby not being conducive to improving the durability of the catalyst.

[0120] The preparation method of the third aspect of the embodiment of the present invention has no particular restrictions on the method for achieving active metal loading in step S302, and can be any active metal loading method in the related art. For example, a loading method such as a liquid phase reduction method, a vacuum impregnation method, an equal volume impregnation method, etc. can be used to load the active metal precursor on the oxidized carbon carrier, and then after drying, sintering, etc., the active metal is loaded to obtain the first catalyst.

[0121] For example, in step S302, the active metal can be loaded by liquid phase reduction method. Specifically, the active metal salt is used as a precursor, and the active metal salt is prepared into a solution as a precursor solution to impregnate the oxidized carbon material. The impregnated oxidized carbon material is then dried and sintered to complete the loading of the active metal, thereby obtaining the first catalyst.

[0122] Optionally, the active metal salt may include but is not limited to at least one of platinum salts, ruthenium salts, iridium salts, gold salts, cobalt salts, iron salts, nickel salts, copper salts, cerium salts, manganese salts, palladium salts and silver salts. Wherein, the platinum salt may be selected from at least one of chloroplatinic acid, platinum nitrate, tetraammine platinum nitrate, platinum acetylacetonate and platinum phthalocyanine. The platinum salt may preferably be platinum acetylacetonate and / or platinum phthalocyanine. Wherein, the ruthenium salt may be selected from ruthenium chloride and / or ruthenium acetylacetonate. Wherein, the iridium salt may be selected from at least one of iridium chloride, iridium acetylacetonate and chloroiridic acid. Wherein, the cobalt salt may be selected from at least one of cobalt nitrate, cobalt acetate, cobalt chloride and cobalt acetylacetonate. Wherein, the iron salt may be selected from at least one of ferric nitrate, ferric chloride, ferric acetylacetonate and ferric citrate. Wherein, the nickel salt may be selected from at least one of nickel acetylacetonate, nickel nitrate and nickel dichloride. Other types of first active metal salts are no longer listed one by one.

[0123] Optionally, the mass ratio of the oxidized carbon support to the metal element in the active metal salt is 2:3 to 100:1, and the volume ratio of the active metal salt solution to the saturated impregnation volume of the oxidized carbon support can be 0.1:1 to 2:1.

[0124] In some embodiments, in step S303, the volume percentage of ammonia in the ammonia atmosphere is 1% to 100%, such as 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc. When the proportion of ammonia in the ammonia atmosphere is lower than 1%, it is necessary to increase the insulation temperature of the second sintering treatment, which may be accompanied by agglomeration of the active metal of the catalyst. Preferably, the volume percentage of ammonia in the ammonia atmosphere is 10% to 100%, which is conducive to increasing the number of nitrogen-containing functional groups and nitrogen atoms doped on the surface of the fuel cell catalyst.

[0125] For example, the ammonia atmosphere can be ammonia or a mixture of ammonia and an inert gas, wherein the inert gas can be nitrogen and / or argon. If the latter, the ammonia ratio in the ammonia atmosphere can be regulated by adjusting the flow rate ratio of ammonia and the inert gas. When preparing a small-grain catalyst with high catalytic activity as the goal, it is preferred to use pure ammonia as the ammonia atmosphere for sintering to reduce the insulation temperature of the second sintering treatment and avoid agglomeration of active metals.

[0126] The preparation method of the third aspect of the embodiment of the present invention has no particular restrictions on the atmosphere sintering equipment used in step S303, as long as the second sintering process can be completed. For example, the atmosphere sintering equipment may include but is not limited to equipment with atmosphere sintering functions such as a tubular furnace, a vacuum furnace, an atmosphere furnace, and a muffle furnace, and the sintering carrier may be made of a material that does not react with the ammonia atmosphere and the first catalyst at high temperature.

[0127] In some embodiments, in step S303, the insulation temperature of the second sintering treatment is 100°C to 1000°C, such as 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, etc.; the insulation time of the second sintering treatment is 0.5 hours to 12 hours, such as 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc. In the ammonolysis process of batch materials, the insulation temperature of the second sintering treatment is further preferably 200 to 400°C, and the insulation time of the second sintering treatment is preferably 1 hour to 5 hours. When the ammonolysis temperature is too low, the nitrogen doping ratio of the material is too low, the ammonolysis time is extended, and the production efficiency is reduced. When the ammonolysis temperature is too high, the active metals on the catalyst may agglomerate, which is not conducive to improving the catalytic activity of the finished catalyst.

[0128] A fourth aspect of the embodiments of the present invention provides a fuel cell catalyst obtained by the preparation method of the first aspect, the second aspect or the third aspect.

[0129] Since the preparation method of the first, second or third aspect of the embodiment of the present invention is adopted, the dispersion uniformity and intra-pore loading ratio of the active metal in the fuel cell catalyst of the fourth aspect of the embodiment of the present invention are relatively high. Therefore, compared with the fuel cell catalyst disclosed in the related art, the fuel cell catalyst of the fourth aspect of the embodiment of the present invention has better catalytic activity and durability.

[0130] A fifth aspect of the embodiments of the present invention provides a fuel cell comprising the fuel cell catalyst of the fourth aspect.

[0131] Since the fuel cell catalyst of the fourth aspect of the embodiment of the present invention is used, the fuel cell of the fifth aspect of the embodiment of the present invention has high efficiency and stable operation.

[0132] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.

[0133] Example 1

[0134] (1) Add 50 g of the carbon powder to be treated into a quartz sintering carrier, place the carrier in the center of a tube furnace, and sinter the carbon powder at 500° C. for 2 hours while continuously passing air at a flow rate of 2 L / min to obtain an oxidized carbon carrier.

[0135] (2) a. Take 4 g of the oxidized carbon support of step (1) and mix it with 400 g of water and continue stirring to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3 g of platinum (i.e., the first active metal) with water to a solution of 300 mL, and slowly add it dropwise to the mechanically stirred mixed solution; add sodium borohydride diluted with pure water dropwise to the obtained mixed solution, and stir the obtained mixture for 15 hours; after the stirring is completed, the obtained dispersed solution is repeatedly filtered and purified to obtain a carbon support loaded with platinum salt.

[0136] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80° C. for 12 hours to obtain a catalyst powder.

[0137] c. The catalyst powder obtained in step b is heat treated at 900° C. in hydrogen to obtain a first catalyst.

[0138] (3) a. Take 10 g of the first catalyst prepared in step (2), put it into a quartz sintering carrier, put the carrier into the center of the tube furnace, use a temperature program of 400°C constant temperature for 2 hours, and continuously pass 2 L / min of ammonia to sinter the carbon powder to obtain a second catalyst.

[0139] (4) a. Take 7 g of the second catalyst obtained in step (3) and mix it with 400 g of water, and then continue to stir to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3 g of platinum (i.e., the second active metal) with water to a 300 mL solution, and slowly add it dropwise to the mechanically stirred mixed solution; add sodium borohydride diluted with pure water dropwise to the obtained mixed solution, and stir the obtained mixture for 15 hours; after the stirring is completed, the obtained dispersed solution is repeatedly filtered and purified to obtain a carbon carrier loaded with platinum salt.

[0140] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80 ° C for 12 hours to obtain a catalyst powder;

[0141] c. The catalyst powder obtained in step b is heat treated at 900°C in hydrogen to obtain a finished catalyst.

[0142] Based on the total mass of the finished catalyst being 100%, the total loading of the active metals is 60%; and the ratio of the loading of the first active metal to the loading of the second active metal is 1:1.

[0143] Example 2

[0144] (1) Add 50 g of the to-be-treated carbon powder identical to step (1) of Example 1 into a quartz sintering carrier, place the carrier into the center of a tube furnace, and sinter the carbon powder using a temperature program of 500° C. for 2 hours while continuously passing air at a flow rate of 2 L / min to obtain an oxidized carbon carrier.

[0145] (2) Take 10 g of the oxidized carbon carrier of step (1) and put it into a quartz sintering carrier, place the carrier in the center of a tube furnace, adopt a temperature program of 400°C constant temperature for 2 hours, and continuously introduce 2 L / min of ammonia to sinter the carbon powder to obtain an ammonia-decomposed carbon carrier.

[0146] (3) a. Take 2 g of the carbon support after aminolysis in step (2) and mix it with 400 g of water and continue stirring to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3 g of platinum with water to a 300 mL solution, slowly add it dropwise to the mechanically stirred mixed solution, add sodium borohydride diluted with pure water dropwise to the obtained mixed solution, and stir the obtained mixture for 15 hours; after the stirring is completed, the obtained dispersed solution is repeatedly filtered and purified to obtain a carbon support loaded with platinum salt.

[0147] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80° C. for 12 hours to obtain a catalyst powder.

[0148] c. The catalyst powder obtained in step b is heat treated at 900°C in hydrogen to obtain a finished catalyst.

[0149] Based on the total mass of the finished catalyst being 100%, the total loading of active metals is 60%.

[0150] Example 3

[0151] (1) Add 50 g of the to-be-treated carbon powder identical to step (1) of Example 1 into a quartz sintering carrier, place the carrier into the center of a tube furnace, and sinter the carbon powder using a temperature program of 500° C. for 2 hours while continuously passing air at a flow rate of 2 L / min to obtain an oxidized carbon carrier.

[0152] (2) a. Take 2 g of the oxidized carbon support of step (1) and mix it with 400 g of water and continue stirring to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3 g of platinum with water to a 300 mL solution, slowly add it dropwise to the mechanically stirred mixed solution, add sodium borohydride diluted with pure water dropwise to the obtained mixed solution, and stir the obtained mixture for 15 hours; after the stirring is completed, the obtained dispersed solution is repeatedly filtered and purified to obtain a carbon support loaded with platinum salt.

[0153] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80° C. for 12 hours to obtain a catalyst powder.

[0154] c. The catalyst powder obtained in step b is heat treated at 900° C. in hydrogen to obtain a first catalyst.

[0155] (3) a. Take 10 g of the first catalyst prepared in step (2), put it into a quartz sintering carrier, put the carrier into the center of the tube furnace, use a temperature program of 400°C constant temperature for 2 hours, and continuously pass 2 L / min of ammonia to sinter the carbon powder to obtain a finished catalyst.

[0156] Based on the total mass of the finished catalyst being 100%, the total loading of active metals is 60%.

[0157] Example 4

[0158] The preparation method of this embodiment is the same as that of Embodiment 1, except that the ratio of the loading amount of the first active metal to the loading amount of the second active metal is 0.5:1.

[0159] Example 5

[0160] The preparation method of this embodiment is the same as that of Embodiment 1, except that the ratio of the loading amount of the first active metal to the loading amount of the second active metal is 2:1.

[0161] Example 6

[0162] The preparation method of this embodiment is the same as that of embodiment 1, except that the air sintering temperature in step (1) is 400°C.

[0163] Example 7

[0164] The preparation method of this embodiment is the same as that of embodiment 1, except that the temperature of ammonia sintering in step (3) is 200°C.

[0165] Comparative Example 1

[0166] The same carbon powder to be treated as in step (1) of Example 1.

[0167] Comparative Example 2

[0168] Take 10 g of the same carbon powder to be treated as in step (1) of Example 1 and put it into a quartz sintering carrier. Put the carrier into the center of the tube furnace, use a temperature program of 400°C constant temperature for 2 hours, and continuously introduce 2L / min of ammonia to sinter the carbon powder to obtain a carbon carrier after ammonolysis.

[0169] Comparative Example 3

[0170] a. Take 4g of the same carbon powder to be treated as in step (1) of Example 1 and mix with 400g of water and continue stirring to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3g of platinum with water to a 300mL solution, slowly drop it into the mechanically stirred mixed solution, drop sodium borohydride diluted with pure water into the obtained mixed solution, and stir the obtained mixture for 15 hours. After the stirring is completed, the obtained dispersed solution is repeatedly filtered and purified to obtain a carbon carrier loaded with platinum salt;

[0171] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80 ° C for 12 hours to obtain a catalyst powder;

[0172] c. The catalyst powder obtained in step b is heat treated at 900°C in hydrogen to obtain a finished catalyst.

[0173] Comparative Example 4

[0174] (1) Add 50 g of the to-be-treated carbon powder as in Example 1 into a quartz sintering carrier, place the carrier in the center of a tube furnace, maintain a constant temperature of 500° C. for 2 hours, and continuously introduce 2 L / min of air to sinter the carbon powder to obtain an oxidized carbon carrier.

[0175] (2) a. Take 4 g of the oxidized carbon material of step (1) and mix it with 400 g of water, then continue to stir to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3 g of platinum with water to make 300 mL of solution, slowly add it dropwise to the mechanically stirred mixed solution, add sodium borohydride diluted with pure water dropwise to the obtained mixed solution, and stir the obtained mixture for 15 hours; after the stirring is completed, repeatedly filter and purify the obtained dispersed solution to obtain a carbon carrier loaded with platinum salt.

[0176] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80° C. for 12 hours to obtain a catalyst powder.

[0177] c. The catalyst powder obtained in step b is heat treated at 900° C. in hydrogen to obtain a first catalyst.

[0178] (3) a. Take 7 g of the first catalyst obtained in step (2) and mix it with 400 g of water and continue stirring to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3 g of platinum with water to a 300 mL solution, slowly add it dropwise to the mechanically stirred mixed solution, add sodium borohydride diluted with pure water dropwise to the obtained mixed solution, and stir the obtained mixture for 15 hours; after the stirring is completed, the obtained dispersed solution is repeatedly filtered and purified to obtain a carbon carrier loaded with platinum salt.

[0179] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80 ° C for 12 hours to obtain a catalyst powder;

[0180] c. The catalyst powder obtained in step b is heat treated at 900°C in hydrogen to obtain a finished catalyst.

[0181] Comparative Example 5

[0182] (1) Add 50 g of the to-be-treated carbon powder as in Example 1 into a quartz sintering carrier, place the carrier in the center of a tube furnace, maintain a constant temperature of 500° C. for 2 hours, and continuously introduce 2 L / min of air to sinter the carbon powder to obtain an oxidized carbon carrier.

[0183] (2) a. Take 2 g of the oxidized carbon support of step (1) and mix it with 400 g of water and continue stirring to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3 g of platinum with water to a 300 mL solution, slowly add it dropwise to the mechanically stirred mixed solution, add sodium borohydride diluted with pure water dropwise to the obtained mixed solution, and stir the obtained mixture for 15 hours; after the stirring is completed, the obtained dispersed solution is repeatedly filtered and purified to obtain a carbon support loaded with platinum salt.

[0184] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80° C. for 12 hours to obtain a catalyst powder.

[0185] c. The catalyst powder obtained in step b is heat treated at 900°C in hydrogen to obtain a finished catalyst.

[0186] The loading amount of active metal in the finished catalyst of this comparative example is the same as that in Example 1.

[0187] Comparative Example 6

[0188] (1) Add 50 g of the to-be-treated carbon powder as in Example 1 into a quartz sintering carrier, place the carrier into the center of a tube furnace, maintain a constant temperature of 400° C. for 2 hours, and continuously introduce ammonia gas at a rate of 2 L / min to sinter the carbon powder to obtain a catalyst after ammonolysis.

[0189] (2) a. Take 2 g of the catalyst after ammonolysis obtained in step (1) and mix it with 400 g of water and continue stirring to obtain a mixed solution; dilute the chloroplatinic acid solution containing 3 g of platinum with water to a 300 mL solution, slowly add it dropwise to the mechanically stirred mixed solution, add sodium borohydride diluted with pure water dropwise to the obtained mixed solution, and stir the obtained mixture for 15 hours; after the stirring is completed, the obtained dispersed solution is repeatedly filtered and purified to obtain a carbon carrier loaded with platinum salt.

[0190] b. The carbon support loaded with platinum salt obtained in step a was dried in a vacuum oven at 80 ° C for 12 hours to obtain a catalyst powder;

[0191] c. The catalyst powder obtained in step b is heat treated at 900°C in hydrogen to obtain a finished catalyst.

[0192] The loading amount of active metal in the finished catalyst in this comparative example is the same as that in Example 1.

[0193] Comparative Example 7

[0194] The preparation method of this comparative example is the same as that of Example 1, except that concentrated nitric acid is used in step (1) to perform oxygen doping instead of air oxidation.

[0195] test:

[0196] (1) The carbon powder to be treated, the intermediate product and the finished catalyst in the above-mentioned embodiments and comparative examples were subjected to C, O and N element analysis to obtain the element ratio of the material; the carbon powder to be treated, the intermediate product and the finished catalyst in the above-mentioned embodiments and comparative examples were subjected to nitrogen isothermal adsorption and desorption characterization to obtain the specific surface area of ​​the material; the carbon powder to be treated, the intermediate product and the finished catalyst in the above-mentioned embodiments and comparative examples were subjected to XRD characterization to obtain the Pt average particle size of the material. The above results are shown in Table 1.

[0197] (2) The finished catalysts of each embodiment and comparative example were subjected to oxygen reduction rotating disk electrode test. The results are as follows: Figure 1 And as shown in Table 2.

[0198] (3) The finished catalysts of each embodiment and comparative example were subjected to a three-electrode system electrochemical square wave durability test. The results are as follows: Figure 2 And as shown in Table 2.

[0199] Table 1

[0200]

[0201]

[0202] Table 2

[0203]

[0204] The data in Tables 1 and 2 show that:

[0205] (1) There is a large difference in oxygen content between the to-be-treated carbon powder of comparative example 1 and the oxidized carbon material of step (1) of example 1, indicating that the oxidation treatment process in the preparation method of example 1 of the present invention significantly increases the number of oxygen-containing functional groups on the surface of the carbon powder or the proportion of oxygen element doping, while increasing the specific surface area of ​​the carbon powder material, providing more loading sites for active metals.

[0206] (2) There is a significant difference in nitrogen content between the carbon material after ammoniolysis of Comparative Example 2 and the carbon material after ammoniolysis of step (2) of Example 2, indicating that the efficiency of doping nitrogen in the carbon powder after oxidation treatment through ammoniolysis treatment in the preparation method of Example 2 is higher.

[0207] (3) The difference in specific surface area between the finished catalyst of Comparative Example 3 and the first catalyst of step (2) of Example 1 is relatively large, indicating that when the oxidized carbon carrier in the preparation method of Example 1 is used as a carrier, a larger proportion of the active metal Pt will be loaded into the pores, causing the specific surface area of ​​the material before and after loading to decrease more.

[0208] (4) There is a significant difference in the average Pt particle size between the finished catalyst of Comparative Example 4 and the finished catalyst of step (4) of Example 1. The average Pt particle size of the finished catalyst of step (4) of Example 1 is smaller, indicating that the increase in the nitrogen doping ratio on the material treated with ammonolysis in the preparation method of Example 1 has an anchoring effect on the active metal Pt, making the dispersion of the active metal higher. The finished catalyst of Comparative Example 4 and the finished catalyst of step (4) of Example 1 were subjected to electrochemical oxygen reduction activity characterization and low-potential square wave durability test. The results are as follows: Figure 1 and Figure 2 As shown, the finished catalyst of step (4) of Example 1 has higher oxygen reduction mass specific activity and better durability, indicating that the catalyst prepared by the step-by-step loading method of the high oxygen and nitrogen doped carrier of Example 1 has higher catalytic performance and better durability.

[0209] (5) It should be noted that the inventors have tried to adjust the oxygen doping step in Comparative Example 5, hoping that the oxygen doping content in Comparative Example 5 is substantially equal to the sum of the nitrogen and oxygen doping contents in Example 1, and then compared it with Example 1, but found that this result does not occur. Similarly, the inventors have also tried to adjust the nitrogen doping step in Comparative Example 6, hoping that the nitrogen doping content in Comparative Example 6 is substantially equal to the sum of the nitrogen and oxygen doping contents in Example 1, and then compared it with Example 1, but found that this result does not occur either. Therefore, the fuel cell catalyst preparation method of only oxygen doping in Comparative Example 5 or only nitrogen doping in Comparative Example 6 can achieve a low doping content of heteroatoms (nitrogen or oxygen) in the carbon material, while the preparation method of the second aspect of the embodiment of the present invention can achieve high-content heteroatom (nitrogen and oxygen) doping in the carbon material. From the comparison between Comparative Example 5 and Comparative Example 6 and Examples 1 to 5 in Table 2, it can be seen that the finished catalysts of Examples 1 to 5 have higher oxygen reduction mass specific activity and better durability, which means that compared with the method of only doping nitrogen or only doping oxygen in the related art, the preparation method of Examples 1 to 5 of the present application achieves high-content heteroatom (nitrogen and oxygen) doping, which effectively improves the catalytic performance of the catalyst.

[0210] (6) By comparing Example 1 and Comparative Example 7 in Tables 1 and 2, it can be seen that the preparation method of Example 1 of the present invention adopts air oxidation instead of concentrated nitric acid oxidation, which increases the oxygen-containing functional groups and oxygen atom doping number on the surface of the carbon carrier after oxidation as reaction sites for the ammonolysis treatment of nitrogen doping, significantly improves the efficiency of ammonolysis treatment of nitrogen doping, and greatly reduces the difficulty of nitrogen doping of the carrier. This method is a mass production approach to achieve controllable nitrogen doping of carbon carriers.

[0211] In summary, when the ratio of nitrogen and oxygen content on the carbon carrier is within an appropriate range, the carbon powder used as a catalyst carrier can not only improve the dispersion of metal components, increase the intrapore loading of active components and reduce resin poisoning, but also improve the uniform dispersion of the resin, reduce mass transfer resistance and thus improve the catalytic efficiency of the catalyst active sites.

[0212] Therefore, the commercial carbon powder post-treatment method of the embodiment of the present invention is safe and reliable, easy to mass produce, and has an adjustable nitrogen and oxygen doping ratio, which is of great significance for the preparation of supported intrapore-supported high-activity and high-durability fuel cell catalysts.

[0213] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0214] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a fuel cell catalyst, characterized in that: The following steps are involved: S101, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier; S102, loading a first active metal on the oxidized carbon support to obtain a first catalyst; S103, performing a second sintering treatment on the first catalyst in an ammonia atmosphere to obtain a second catalyst; S104, loading a second active metal onto the second catalyst to obtain the fuel cell catalyst.

2. A method for preparing a fuel cell catalyst, characterized in that: The following steps are involved: S201, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier; S202, subjecting the oxidized carbon support to a second sintering treatment in an ammonia atmosphere to obtain an ammonolyzed carbon support; S203, loading active metals onto the carbon carrier after the ammonolysis to obtain the fuel cell catalyst.

3. A method for preparing a fuel cell catalyst, characterized in that: The following steps are involved: S301, performing a first sintering treatment on the carbon material in an oxygen atmosphere to obtain an oxidized carbon carrier; S302, loading an active metal onto the oxidized carbon support to obtain a first catalyst; S303, performing a second sintering treatment on the first catalyst in an ammonia atmosphere to obtain the fuel cell catalyst.

4. The preparation method according to claim 1, characterized in that: Based on the total mass of the fuel cell catalyst being 100%, the sum of the mass percentages of the first active metal and the second active metal is greater than 0 and less than or equal to 80%; Optionally, the mass ratio of the first active metal to the second active metal is (0.1-10):1; Optionally, the first active metal is selected from at least one of platinum, ruthenium, iridium, gold, cobalt, iron, nickel, copper, cerium, manganese, palladium and silver; Optionally, the second active metal is selected from at least one of platinum, ruthenium, iridium, gold, cobalt, iron, nickel, copper, cerium, manganese, palladium and silver.

5. The preparation method according to claim 2 or 3, characterized in that: The active metal is selected from at least one of platinum, ruthenium, iridium, gold, cobalt, iron, nickel, copper, cerium, manganese, palladium and silver.

6. The preparation method according to any one of claims 1 to 3, characterized in that: The carbon material is selected from at least one of carbon black, graphitized carbon, graphite, carbon nanotubes, graphene and a material having a carbon coating layer.

7. The preparation method according to any one of claims 1 to 3, characterized in that: The volume percentage of oxygen in the oxygen atmosphere is 1% to 100%; Optionally, the holding temperature of the first sintering treatment is 200° C. to 800° C., and the holding time of the first sintering treatment is 0.5 hour to 12 hours; Preferably, the holding temperature of the first sintering treatment is 500° C. to 700° C., and the holding time of the first sintering treatment is 1 hour to 5 hours.

8. The preparation method according to any one of claims 1 to 3, characterized in that: The volume percentage of ammonia in the ammonia atmosphere is 1% to 100%; Optionally, the insulation temperature of the second sintering treatment is 100° C. to 1000° C., and the insulation time of the second sintering treatment is 0.5 hour to 12 hours.

9. A fuel cell catalyst, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8.

10. A fuel cell, characterized in that: Contains the fuel cell catalyst according to claim 9.